HARMONISASI MATERI MUATAN BERDASARKAN NILAI DAN PRINSIP HAK ASASI MANUSIA DALAM PEMBENTUKAN PERATURAN DAERAH DI INDONSESIA - Sherly Kurnia Fitri (Ensiklopedia Education Review, 2022)
Regional regulations are products of laws and regulations that arise as a result of regional autonomy policies according to the principle of decentralization so that regions have more or less the desire to advance their regions by issuing regional regulations that benefit their regions. Human rights content material in this case plays a very important role so that the ego advances the area so that it continues to run according to the rules and does not eliminate harmony with other laws and regulations or above. This study will discuss harmonization of content based on human rights values and principles in the formation of regional regulations in Indonesia using normative juridical research methods. The results of the study found that the Directorate General of Legislation of the Ministry of Law and Human Rights in its implementation relied on the role of the Regional Office of the Ministry of Law and Human Rights. The Regional Office of the Ministry of Law and Human Rights plays a role in the planning and formation of regional legislation products so that these regional legislative products remain within the unity of the national legal system which is subject to the values and principles of human rights. In particular, the Legal Sector has the task of carrying out activities in the field of preparing legal planning materials, and fostering legal documentation and information networks and coordinating regional legislation programs in accordance with applicable laws and regulations.Keywords: Harmonization, Values, Principles, Human Rights, Regional Regulations